Junior High School Students’ Difficulties in Reading English Texts - Khafidhoh Khafidhoh; Novia Nurul Hikmah Abdullah (Universitas Ahmad Dahlan, 2022)
In learning English, students are directed to have skills in reading English texts because students can understand the information through reading. This study investigates the students’ perception of the factors causing the students to have difficulties in reading English texts and the strategies the students use to overcome the difficulties in reading English texts. This research belongs to descriptive qualitative research, and the research data sources are interviews and questionnaires. The data were taken from the student in 8th grade of SMP Negeri 1 Bungku. There were 15 students answered the questionnaire, but only 13 joined the interview. The data were analyzed by reducing data, displaying data, and drawing conclusions. The results of this study indicate that the students' perception of the students’ difficulties in reading English text includes the lack of motivation from the teacher to improve the students’ reading skills and the lack of the students' vocabulary and pronunciation. Moreover, the strategies the students used to overcome their difficulties were taking notes of some important points in the text and the newly acquired vocabulary, translating them using google translate, and practicing them with friends.